Enhanced Cognition and Neurogenesis in miR-146b Deficient Mice - Keerthana Chithanathan; Kelli Somelar; Monika Jürgenson; Tamara Žarkovskaja; Kapilraj Periyasamy; Ling Yan; Nathaniel Magilnick; Mark P. Boldin; Ana Rebane; Li Tian; Alexander Zharkovsky (Cells, 2022)
The miR-146 family consists of two microRNAs (miRNAs), miR-146a and miR-146b, which are both known to suppress a variety of immune responses. Here in this study, we show that miR-146b is abundantly expressed in neuronal cells, while miR-146a is mainly expressed in microglia and astroglia of adult mice. Accordingly, miR-146b deficient (Mir146b-/-) mice exhibited anxiety-like behaviors and enhanced cognition. Characterization of cellular composition of Mir146b-/- mice using flow cytometry revealed an increased number of neurons and a decreased abundancy of astroglia in the hippocampus and frontal cortex, whereas microglia abundancy remained unchanged. Immunohistochemistry showed a higher density of neurons in the frontal cortex of Mir146b-/- mice, enhanced hippocampal neurogenesis as evidenced by an increased proliferation, and survival of newly generated cells with enhanced maturation into neuronal phenotype. No microglial activation or signs of neuroinflammation were observed in Mir146b-/- mice. Further analysis demonstrated that miR-146b deficiency is associated with elevated expression of glial cell line-derived neurotrophic factor (Gdnf) mRNA in the hippocampus, which might be at least in part responsible for the observed neuronal expansion and the behavioral phenotype. This hypothesis is partially supported by the positive correlation between performance of mice in the object recognition test and Gdnf mRNA expression in Mir146b-/- mice. Together, these results show the distinct function of miR-146b in controlling behaviors and provide new insights in understanding cell-specific function of miR-146b in the neuronal and astroglial organization of the mouse brain.